2003
DOI: 10.1002/chin.200344121
|View full text |Cite
|
Sign up to set email alerts
|

Formylchromone Derivatives as a Novel Class of Protein Tyrosine Phosphatase 1B Inhibitors.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Appropriately substituted biphenyl, when docked into the PTP1B enzyme, gives satisfactory attachment to the binding sites of PTP1B. This new compound, VMNS2e, exhibited a glucose‐lowering effect in alloxan‐induced diabetic mice, 8 which was comparable to the compounds having the biphenyl moiety reported earlier 1–6 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Appropriately substituted biphenyl, when docked into the PTP1B enzyme, gives satisfactory attachment to the binding sites of PTP1B. This new compound, VMNS2e, exhibited a glucose‐lowering effect in alloxan‐induced diabetic mice, 8 which was comparable to the compounds having the biphenyl moiety reported earlier 1–6 …”
Section: Discussionmentioning
confidence: 66%
“…Biphenyl was selected in our scheme as a pharmacophore, and various biphenyl derivatives were synthesized in our laboratory. A literature survey showed various compounds with anti‐hyperglycemic activity having biphenyl moiety 1–7 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that molecules containing biphenyl as pharmacophore exhibited significant PTP 1B inhibition. X-ray crystallographic studies also indicated that molecules containing biphenyl bind to PTP 1B active site and are held in place through weak hydrogen bonding and van der Waals interactions formed within two hydrophobic domains [28][29][30][31][32]. In our present study, biphenyl has been selected as one of the active pharmacophore for inhibition of PTP 1B.…”
Section: Introductionmentioning
confidence: 79%
“…A successful 3D-QSAR study was performed to establish relationship between the 3D-pharmacophoric features and PTP 1B inhibitory activity of formylchromane derivatives (8,9). The present 3D-QSAR investigation was performed with the data set of 36 molecules having a well-defined PTP 1B inhibitory activity cited as IC 50 values in lM concentrations.…”
Section: Data Set For Analysismentioning
confidence: 99%
“…It can also be explored to identify and describe important structural requirements of the molecules that are pertinent to optimal biological activity. Recently, various derivatives of formylchromanes were reported that possess remarkably selective PTP 1B inhibitory activity with IC 50 values ranging as low as 1.0 lM (8,9). In this study, highly predictive atom-based 3D-QSAR models have been generated using PHASE module of Schr€ odinger suite for a set of formylchromane derivatives as PTP 1B inhibitors.…”
mentioning
confidence: 99%